Who Is Metabolizing What? Discovering Novel Biomolecules in the Microbiome and the Organisms Who Make Them - Couvillion, Sneha P.; Agrawal, Neha; Colby, Sean M.; Brandvold, Kristoffer R.; Metz, Thomas O. (Frontiers in Cellular and Infection Microbiology, 2020)
Even as the field of microbiome research has made huge strides in mapping microbial community composition in a variety of environments and organisms, explaining the phenotypic influences on the host by microbial taxa – both known and unknown – and their specific functions still remain major challenges. A pressing need is the ability to assign specific functions in terms of enzymes and small molecules to specific taxa or groups of taxa in the community. This knowledge will be crucial for advancing personalized therapies based on the targeted modulation of microbes or metabolites that have predictable outcomes to benefit the human host. This perspective article advocates for the combined use of standards-free metabolomics and activity-based protein profiling strategies to address this gap in functional knowledge in microbiome research via the identification of novel biomolecules and the attribution of their production to specific microbial taxa.